(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The integration of digital technologies into education has significantly transformed the process of learning foreign languages and professional terminology. Among various technological tools, video lessons have become one of the most effective methods for teaching terminology due to their visual, auditory, and interactive features. This article examines the role of video lessons in terminology acquisition, analyzes their pedagogical advantages, and discusses their impact on learners’ motivation, comprehension, pronunciation, and retention of specialized vocabulary. The study also explores the effectiveness of multimedia resources and online platforms in improving terminology learning in English language education. The findings indicate that video-based learning creates a more engaging educational environment and contributes to the development of communicative competence and professional language skills.